2019
DOI: 10.1038/s41431-019-0537-8
|View full text |Cite|
|
Sign up to set email alerts
|

New frontiers to cure Alport syndrome: COL4A3 and COL4A5 gene editing in podocyte-lineage cells

Abstract: Alport syndrome (AS) is an inherited genetic disorder characterized by range of alterations from glomerular basement membrane abnormalities up to end-stage renal disease. Pathogenic variants in the collagen α3, α4, and α5 encoding genes are causative both of the autosomal dominant and of the X-linked forms of AS. Podocytes are the only renal cells that are able to produce the COL(IV)a3-a4a5 heterotrimer. We have previously demonstrated how it is possible to isolate podocyte-lineage cells from urine of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…This should prompt the reevaluation of living-donor kidney transplantation guidelines in various genetic kidney diseases [211]. Furthermore, the pathogenicity of splicing variants could be easily confirmed at the transcript level in primary podocytes derived from urine of Alport syndrome patients with intronic variants in COL4A3, COL4A4 or COL4A5 genes [139].…”
Section: Utility Of Urine-derived Epithelial Cells As Models For Genetic Kidney Diseasesmentioning
confidence: 99%
“…This should prompt the reevaluation of living-donor kidney transplantation guidelines in various genetic kidney diseases [211]. Furthermore, the pathogenicity of splicing variants could be easily confirmed at the transcript level in primary podocytes derived from urine of Alport syndrome patients with intronic variants in COL4A3, COL4A4 or COL4A5 genes [139].…”
Section: Utility Of Urine-derived Epithelial Cells As Models For Genetic Kidney Diseasesmentioning
confidence: 99%
“…A 2019 study reported the successful use of CRISPR-Cas9 gene editing in cultured urine-derived podocytes from patients with Alport syndrome. 174 This approach achieved homologous correction in 59% of variant in COL4A5 (Gly624Asp) and 44% of variants in COL4A3 (Gly856Glu) 174 . Exon skipping therapy [G] can also be induced by CRISPR-Cas9, or with splice-blocking antisense oligonucleotides.…”
Section: [H1] Therapy For Gbm-associated Diseasementioning
confidence: 99%
“…Sergio Daga (Medical Genetics, University of Siena, Siena, Italy), from the group of Aelssandra Renieri, has employed a two-plasmid CRISPR/Cas9 genome editing approach, achieving a beneficial and stable correction of the COL4 loss-of-function variants on urine-derived podocyte-lineage cells (Fig. 3B ) [ 55 , 56 ]. In order to translate the in-vitro application into a future in-vivo clinical trial, dogs and mice have been used as preclinical animal models to investigate the safety and efficacy of the system.…”
Section: Gene Therapy Approaches Using Gene Editingmentioning
confidence: 99%